Assistance of the Madura Community Towards a Women-Friendly and Child-Caring Village Karangbayat Village, Sumberbaru District, Jember Regency - Agustina Dewi; Akhmad Sofyan; Dewi Angelina (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Karangbayat Village is one of the villages in Sumberbaru District that has prepared itself to go to one of the DRPPA (Women Friendly and Child Care Villages) in the Jember Regency. In 2023, the Karangbayat Regional Government will start preparing for the reactivation of the Child Task Force and the Gender Mainstreaming Working Group. Departing from the phenomena that have been explained, the Jember University service team carried out service to Karangbayat Village, Sumberbaru District, Jember Regency in the form of socialization about Women-Friendly and Child Care Villages. Through this socialization, it is hoped that Karangbayat Village in 2024 can realize a Women-Friendly and Child Care Village. In the implementation of community service activities for the Madurese ethnic community in Karangbayat Village, Sumberbaru District, Jember Regency, several methods of implementation and assistance will be applied. The stages that will be carried out are the preparation stage, the implementation of assistance, and evaluation.